(untitled) (TEL Tempo, Espaço e Linguagem, 2024)
This research analyzes the memories of subjects from the Brazilian semi-arid region about the use of the facheiro cactus in school meals in Boqueirão/PB. The objective is to contribute to food security and reflect on socio-environmental problems. We access these memories in the field of Oral History and use the methodology of discourse analysis. When we write down the experiences of the people of Boqueirão, we find that the food use of the facheiro reconfigures spaces and can contribute to a sustainable world. Keywords: History. Sustainability. Feeding. Cactus. Facheiro.